2020
DOI: 10.1667/rr15540.1
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Impairments in Mice Subjected to Irradiation and Chemotherapy

Abstract: Radiotherapy, surgery and the chemotherapeutic agent temozolomide (TMZ) are frontline treatments for glioblastoma multiforme (GBM). However beneficial, GBM treatments nevertheless cause anxiety or depression in nearly 50% of patients. To further understand the basis of these neurological complications, we investigated the effects of combined radiotherapy and TMZ chemotherapy (combined treatment) on neurological impairments using a mouse model. Five weeks after combined treatment, mice displayed anxiety-like be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Furthermore, a single dose of whole brain radiotherapy was used in current studies to follow-up on the significant body of work from our laboratory implementing such a dosing scheme. While previous studies (59,60) have shown that fractionated irradiation causes RICD, follow-up studies aimed at determining how EVs might mitigate RICD after dose fractionation and in female mice are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a single dose of whole brain radiotherapy was used in current studies to follow-up on the significant body of work from our laboratory implementing such a dosing scheme. While previous studies (59,60) have shown that fractionated irradiation causes RICD, follow-up studies aimed at determining how EVs might mitigate RICD after dose fractionation and in female mice are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of TMZ on various cognitive functions has been investigated previously in clinical studies (memory, attention, and overall life quality of patients) [15,16] and in animal models (parameters related to depression and anxiety) [17,18]. However, the effect of the drug on locomotor activity has not been studied enough, with research mainly focused on young animals [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Data on long-term TMZ effects on health-related quality of life and cognitive function are quite controversial and demonstrate both no negative side effects during the chemotherapy [14,15] and significant depression starting at the third month after adjuvant TMZ therapy [16]. It was shown that mice treated with a regimen of TMZ similar to humans demonstrate anxiety-and depression-like behaviour [17] and behavioural and biochemical changes that have relevance to the development of depression [18]. Another important parameter of a high life quality after TMZ treatment is physical activity that might be compromised by TMZ chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Open Field Test (OFT) was performed in a fully lit behavior room, mice were placed in an empty white arena with no habituation or prior extensive handling. Exploration and distance traveled was measured over 5 minutes using Ethovision XT (Noldus) software as described previously [60]. Light Dark Box (LDB) was performed in a fully lit behavior room, mice were placed in an arena with an open white 'light' portion connected to a closed black 'dark' compartment.…”
Section: Methodsmentioning
confidence: 99%